Does Islamic Banking Contribute to Increasing Public Welfare? Evidence from Indonesian Province Panel Data - Rezeki, Fuzi Amali Sri; Limayyasa, Risma; Mufti, Fauzan Ali; Widhansetyati, Purwanti; Syarief, Mochamad Edman; Setiawan, S; Fatoni, Muhammad Iqbal (Universitas Muhammadiyah Surakarta, 2024)
One of the Sustinable Development Goals (SDGs) targets in Indonesia is to increase the level of public welfare that can be represented in GRDP per capita. Therefore, the purpose of this study is to determine whether Islamic banking through Islamic Commercial Banks (BUS), Islamic Business Units (UUS) and Sharia Rural Banks (BPRS) in 33 provinces in Indonesia, has contributed to GRDP per capita during the 2015-2022 period. GRDP per capita as a proxy indicator for the level of public welfare to encourage the achievement of the sustainable development goals (SDGs) target. This study uses panel data regression analysis because the data is time series and cross section. The size of the Islamic banking contribution uses Islamic Bank Office (IBO), Financing and Third-Party Funds (TPF) variables in 33 provinces in Indonesia. Meanwhile, the size of the welfare level of a region uses Gross Regional Domestic Product (GRDP) per capita data. The findings of this study show that the IBO, financing, and TPF variables simultaneously have a significant positive effect on GRDP. However, partially, the IBO variable has a significant negative effect on GRDP, the financing variable has a significant positive effect on GRDP, and the TPF variable has no effect on GRDP.